1985
DOI: 10.1148/radiology.154.3.3969476
|View full text |Cite
|
Sign up to set email alerts
|

Acute injury of the ligaments of the knee: magnetic resonance evaluation.

Abstract: Eleven acutely injured knees and 13 normal knees were examined by magnetic resonance imaging (MRI) to assess the value of this modality in detecting acute ligamentous injury of the knee. The presence of torn ligaments in the injured knees was determined by arthroscopy and/or arthrotomy in ten cases and clinical follow-up in one case. The anterior and posterior cruciate ligaments (ACL and PCL) were demonstrated by sagittal spin echo (SE) images through the intercondylar notch (TE = 30 ms; TR = 2,000 ms). The ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…Tear of the anterior cruciate ligament (ACL) [ Figure 3] -is one of the most common injuries to the knee [1]. The biomechanics involved in ACL tear are -External rotation and abduction with hyperextension; direct forward displacement of the tibia; internal rotation with the knee in full extension.…”
Section: Discussionmentioning
confidence: 99%
“…Tear of the anterior cruciate ligament (ACL) [ Figure 3] -is one of the most common injuries to the knee [1]. The biomechanics involved in ACL tear are -External rotation and abduction with hyperextension; direct forward displacement of the tibia; internal rotation with the knee in full extension.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by David A.Turner et.al 11 in 1985, they concluded that MR imaging may be useful in detecting acute injury of ligaments of the knee by comparing 13 cases with the arthroscopy and/or arthrotomy . In a study done by Lee JK et.al 12 in 1988, they compared the MR with the findings of two commonly applied clinical tests of ACL instability: the Lachman test and the anterior drawer test and arthroscopy got the following results.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Injuries are identified by an increased signal intensity due to edema and hemorrhage, increased thickness, abnormal configuration, and/or discontinuity of the ligament [6,20,22] (Fig. 11).…”
Section: Collateral Ligament Complexesmentioning
confidence: 99%